The Scientific of Macro Maqasid in Developing of Social Financing Products - FISOL, WAN NAZJMI MOHAMED; BAKAR, MARINA ABU; RAHIM, AHMAD KHILMY BIN ABDUL (The journal of contemporary issues in business and government, 2021)
The maqasid-cum-masalih theory has been developed to facilitate the Shari‘ah scholars in deducing more appropriate Islamic legal opinion(ijtihad) in Islamic banking and finance matters in light of the objectives of Shari‘ah (maqasid al-Shari‘ah). The purpose of this paper is to study the macro maqasid based on the maqasid-cum-masalih theory that are used in the development of Islamic financial products as well as social financing products. Research methodology is a fundamental part of any research work and is vital for the success of research. The research design to be utilized the quantitative method by using questionnaire method. This method has been used to obtain perceptions of the Shari’ah advisory and supervisory boards’ members on viability and applicability of macro maqasid perspective based on the maqasid-cum- masalih theory. The macro maqasid (Islamic economics objectives) should be in conformity with the maqasid-cum-masalih theory as well as the objectives of Shari‘ah (maqasid al-Shari‘ah) in developing more social financing products in Islamic banking and financial institutions. The paper shows that the using of macro maqasid based on the maqasid-cum-masalih theory can be used by the Shari’ah advisory and supervisory boards’ members to developing more social financing products in Islamic banking and financial institutions.